KOMPOSISI KIMIA DAN KANDUNGAN PIGMEN Spirulina fusiformis PADA UMUR PANEN YANG BERBEDA DALAM MEDIA PUPUK - Iriani Setyaningsih; Andika Tri Saputra; . Uju (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2011)
Spirulina fusiformis is bluegreen alga which grows in freshwater. The aims of the research were to observe the growth curve, chemical composition and pigment content of S. fusiformis cultivated in fertilized media and harvested on different times (18 and 32 days). S. fusiformis cultivated in fertilized media had  ve phases of growth. The end of exponential and stationary phases were achieved on days 15 and 24, respectively. The S. fusiformis harvested on 18 days contained 52.72% protein, 17.19% carbohydrate, 8.47% fat, 6.24% ash, 5.5% phycocyanin, and 0,47% chlorophyll, while harvested on 32 days contained 55.22% protein, 21.32% carbohydrate, 8.67% fat, 9.57% ash, 4.68% phycocyanin, and 0.43% chlorophyll. In this study, S. fusiformis contained 17 amino acids, 9 of them are essential amino acids.Keywords: Spirulina fusiformis, fertilized, chemical composition, harvesting age, pigment